Bulletin d'information du Bureau permanent du Front de libération de Mozambique à Alger (Liberation movements in lusophone Africa : serials from the collection of Immanuel Wallerstein., 1964)
No. 3 is a reprint of "Boletim nacional de informação no. 7, publicado pelo Departamento de Informação e Propaganda da FRELIMO, em Dar es Salaam, Tanganyika.